Herpes zoster in outpatient departments of healthcare centers in India: a review of literature. Issue 11 (2nd November 2021) - Patki, Anil; Vora, Agam; Parikh, Raunak; Kolhapure, Shafi; Agrawal, Ashish; Dash, Resham
ABSTRACT: In India, although incidence of Herpes zoster has not been assessed, regional cases have been reported. We revisited the peer-reviewed literature on clinical cases of HZ to depict the trends in population characteristics, disease presentation, and predisposing factors for the disease in India. Systematically conducted literature search yielded 27 studies, published between January 2011 and May 2020, reporting 3124 HZ clinical cases, with high proportions in older adults (>50 years of age: 15.0–81.3%). Thoracic dermatome was consistently reported as the most frequent site affected by HZ (38.9–71.0%). Post-herpetic neuralgia and secondary bacterial infections were the two most frequent complications (10.2–54.7% and 3.5–21.0%, respectively). Despite the paucity of data and gaps in the reporting of HZ cases, available evidence indicate that the disease causes an important burden to older adults in India, suggesting that preventive strategies, along with recommendations to healthcare practitioners, can help mitigate the burden of HZ. PLAIN LANGUAGE SUMMARY: What is the context? Herpes zoster is caused by reactivation of the varicella virus in sensory gangila usually during older age. The most common complication involve skin and neurological disorders, such as post herpetic neuralgia. Herpes zoster can impact quality of life for months or even years (especially for those >50 years of age). In India, there is a lack of population-based studies on herpes zoster to reflect burden of disease. What is new? We reviewed the literature on clinical cases of herpes zoster in India from last decade and found that: High propotions of older adults (>50 years of age) are reported to have the disease. Thoracic dermatomes and post herpetic neuralgia are common clinical presentation and complication. Post herpetic neuralgia is observed more frequently in older patients. What is the impact? Our review highlights sigificant number of cases of herpes zoster are reported and the disease causes a substantial burden to older adults in India. In view of the growing elderly population in India, the finding of greater proportion of cases in >50 years of age holds importance. Implementation of preventive strategies along with guidance to healthcare pracitioners can help prevent the disease and complications in vulnerable population.